Transferrin-functionalized liposomes for docetaxel delivery to prostate cancer cells - Aires Fernandes, Mariza [UNESP]; O. Eloy, Josimar; Tavares Luiz, Marcela; Ramos Junior, Sergio Luiz; Borges, Júlio César; Rodríguez de la Fuente, Laura; Ortega-de San Luis, Clara; Maldonado Marchetti, Juliana; Santos-Martinez, Maria J.; Chorilli, Marlus [UNESP] (Elsevier, 2021)
Prostate cancer (PC) is the second type of cancer, causing the greatest number of deaths among the male population in the world. An attractive approach to treat PC involves the superficial modification of liposomes with specific ligands to overexpressed receptors on the surfaces of tumor cells, such as transferrin receptors (TFR's). To our knowledge, this is the first time that transferrin-functionalized liposomes for delivery of DTX to prostate cancer cells were investigated. In this study, we developed and characterized docetaxel- loaded liposomes functionalized with transferrin (LIP-DTX-TF) and evaluated their effect on PC cell lines. The results showed that the systems had a nanometric size and the presence of DTX contributed to the reduction of the vesicle size and liposomes were stable. The encapsulation efficiency of DTX was approximately 69 and 37 % for liposomes with and without functionalization, respectively. The functionalization efficiency using TF was 31 %. The functionalization process did not affect the integrity of TF. DTX encapsulated in the liposomes showed slow and sustained release for LIP-DTX and LIP-DTX-TF (51.70 % and 31.97 %, respectively). The in vitro cytotoxicity assay in PC-3 and PNT2 cell lines suggest that LIP-DTX-TF was more toxic to PC-3 than the commercial formulation. Confocal microscopy proved that functionalized liposomes were successfully internalized in PC-3 cells. Furthermore, the interaction of these systems with the TFR's overexpressed on the cell surface was further corroborated using Quartz Crystal Microbalance with Dissipation technology (QCM-D). Therefore, although additional studies in three-dimensional cell models and in vivo xenograft studies are warranted, it can be concluded that the systems developed here are promising candidates for the delivery of docetaxel to prostate cancer cells.
Keywords: Docetaxel; Functionalization; Liposomes; Prostate cancer; QCM-D; Transferrin